2018
DOI: 10.1016/j.jnoncrysol.2018.03.039
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of the atomic structure of glassy Ga10Ge15Te75

Abstract: First-principles molecular dynamics have been employed to highlight the structural properties of glassy Ga 10 Ge 15 Te 75 (GGT), a promising disordered system for infrared applications. Our approach relies entirely on the predictive power of density functional theory, in combination with a careful choice of the exchangecorrelation functional and the account of van der Waals interactions. Glassy GGT can be viewed as a predominantly tetrahedral network, both with respect to Ge and Ga atoms. Te atoms are mostly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…It would be interesting to probe how the structure evolves with composition at lower temperatures and in the amorphous phase, as recently investigated [59]. Work in this direction is in progress.…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to probe how the structure evolves with composition at lower temperatures and in the amorphous phase, as recently investigated [59]. Work in this direction is in progress.…”
Section: Discussionmentioning
confidence: 99%
“…This is exemplified, for instance, by the behavior of glassy GeTe 4 (g-GeTe 4 ), proved to be much more sensitive to dispersion forces (Micoulaut, 2013;Bouzid et al, 2015b) than g-GeSe 4 or g-GeS 4 (Chaker et al, 2018b). Compelling evidence on the impact of vdW forces for Te-rich ternary glasses has been also collected for Ga 10 Ge 15 Te 75 (Chaker et al, 2018a). The above results have been obtained by exploiting the vdW scheme due to Grimme (vdW G ), in particular in the version named D2 (Grimme, 2006).…”
Section: Introductionmentioning
confidence: 96%
“…[29][30][31][32][33][34][35] In particular, BLYP demonstrated a superior performances compared to Perdew, Burke, and Ernzerhof 41 (PBE) functional when modelling Te-based, GeTe 4 , binary chalcogenide system, 42 and led to very good structural models for ternary systems including Ge 2 Sb 2 Te 5 , 43 Ga 4 Sb 6 Te 3 44 and, Ga 10 Ge 15 Te 75 . 45 The core-valence interactions are described by normconserving Troullier and Martins pseudopotentials. 46 The wave functions of the valence electrons were expanded in a plane-wave basis set defined by a kinetic energy cutoff of 40 Ry.…”
Section: First-principles Molecular Dynamics Simulationsmentioning
confidence: 99%
“…In the case of Tebased chalcogenides, it has been shown that van der Waals (vdW) corrections play an essential role in reproducing structural models featuring a good agreement with experiments. 42,45 Therefore, we account for long-range dispersion forces through the DFT-D2 correction term due to Grimme. 47 We resort to the Car-Parrinello molecular dynamics as implemented in the CPMD code.…”
Section: First-principles Molecular Dynamics Simulationsmentioning
confidence: 99%